2017
DOI: 10.1634/theoncologist.2017-0408
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Activity of Pazopanib in Patients with Advanced Desmoplastic Small Round Cell Tumor

Abstract: Desmoplastic small round cell tumor (DSRCT) is an aggressive, usually incurable, soft tissue sarcoma subtype that presents with diffuse abdominal sarcomatosis in adolescents and young adults. This article presents the largest retrospective analysis conducted to date of patients with DSRCT who were treated with an anti‐angiogenic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 38 publications
(44 reference statements)
0
26
0
1
Order By: Relevance
“…One patient who developed complications during adjuvant chemotherapy cycles was transitioned to six planned cycles of pazopanib, and is currently without evidence of disease at 20.7 months from initial diagnosis. Studies have demonstrated that pazopanib is active in DSRCT and well tolerated 39,40 . It remains unknown whether patients with DSRCT benefit from targeted agents, such as pazopanib in the upfront setting, or whether maintenance therapy may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…One patient who developed complications during adjuvant chemotherapy cycles was transitioned to six planned cycles of pazopanib, and is currently without evidence of disease at 20.7 months from initial diagnosis. Studies have demonstrated that pazopanib is active in DSRCT and well tolerated 39,40 . It remains unknown whether patients with DSRCT benefit from targeted agents, such as pazopanib in the upfront setting, or whether maintenance therapy may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Second-line treatment for patients with recurrent disease that have been used are vascular endothelial growth factor (receptor) (VEGF(R))-, mammalian target of rapamycin (mTOR)-, and platelet-derived growth factor receptor (PDGFR)-based targeted therapy. These treatments can again induce favorable, however short-lived, responses (Chen and Feng 2019;Italiano et al 2013;Menegaz et al 2018;Tarek et al 2018;Thijs et al 2010). Overall, treatment results in a 5-year overall survival (OS) rate of 15-25%, which shows the high unmet need for novel treatments in DSRCTs (Bent et al 2016;Subbiah et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…O erlotinibe, um inibidor multialvo da tirosina quinase, levou à resposta parcial em um relato de caso 19 . A atividade contra a doença foi relatada com uso de pazopanibe 20,21 e eribulin 22 . Relato recente demonstrou resultados negativos com imatinibe 23 bevacizumabe também foi relatada [24][25][26] .…”
Section: Discussionunclassified